2019
DOI: 10.5187/jast.2019.61.4.204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary energy and crude protein levels on growth performance, blood profiles, and carcass traits in growing-finishing pigs

Abstract: This experiment was conducted to evaluate the effect of dietary energy and crude protein (CP) levels on growth performance, blood profiles, and carcass traits in growing-finishing pigs. A total of 180 crossbred pigs ([Yorkshire × Landrace] × Duroc) with an average body weight of 30.96 ± 3.068 kg were used for a 12-week feeding trial. Experimental pigs were allotted to a 2 × 3 factorial arrangement using a randomized complete block (RCB) design. The first factor was two levels of dietary metabolizable energy (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
2
15
1
Order By: Relevance
“…The results of this study demonstrated that feeding HE to donkeys enhanced the growth performance in terms of ADG and G/F. Similarly, Ge et al (19) demonstrated that broilers fed HE had greater G/F than the basal energy groups, while Fang et al (20) indicated that G/F decreased as the dietary metabolic energy level decreased over the entire experimental period. Moreover, Ahmad et al (21) found that G/F was significantly higher with an increased dietary energy level.…”
Section: Discussionsupporting
confidence: 60%
“…The results of this study demonstrated that feeding HE to donkeys enhanced the growth performance in terms of ADG and G/F. Similarly, Ge et al (19) demonstrated that broilers fed HE had greater G/F than the basal energy groups, while Fang et al (20) indicated that G/F decreased as the dietary metabolic energy level decreased over the entire experimental period. Moreover, Ahmad et al (21) found that G/F was significantly higher with an increased dietary energy level.…”
Section: Discussionsupporting
confidence: 60%
“…In the present study, BSFLM in feed resulted in better performance of finisher pigs than when fed with conventional feed based on FM. Full-fat BSFLM is rich in CP, amino acids and has a high fat content and thus provides a better source of protein and net energy required for a better growth performance in growing-finishing pigs (Crosbie et al, 2020;Fang et al, 2019;Nekrasov et al, 2018;Yu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, previous studies also reported that the BUN concentration decreased with decreasing CP levels in the diet [ 15 , 61 ]. BUN is a metabolite of protein utilization and is used as an indicator to determine protein digestibility [ 62 ]. Low BUN concentrations are considered to indicate an improvement in protein utilization.…”
Section: Discussionmentioning
confidence: 99%